Migration, Anthropology, and Voice - Graw, Knut (Commoning Ethnography, 2023)
One of the most striking features of contemporary migration to Europe and elsewhere is the almost complete anonymity of its pro-tagonists. The most immediate effect of this anonymity has been the emergence of the figure of the ‘migrant’ in public consciousness with little attention for national and personal backgrounds. A related effect of this anonymization of migration has been that, without personal identity, the individuals concerned also seem to have no history, leading to a rather de-historicized view of migration in the public debate. The present text attempts to counter these tendencies by focusing on an individual narrative of migration between West Africa and Europe, dating back to the late 1980s. On a more theoretical plane, by reflecting on an individual account the article reflects on the question of voice as one of the most central problems of ethnographic representation, both in migration studies and more generall
Keywords: migration; voice; ethnographic writing; West Africa; listening; anthropology; dialogue